Eutectic-based wafer-level-packaging technique for piezoresistive MEMS accelerometers and bond characterization using molecular dynamics simulations. (18th January 2018) - Aono, T; Kazama, A; Okada, R; Iwasaki, T; Isono, Y
Abstract: We developed a eutectic-based wafer-level-packaging (WLP) technique for piezoresistive micro-electromechanical systems (MEMS) accelerometers on the basis of molecular dynamics analyses and shear tests of WLP accelerometers. The bonding conditions were experimentally and analytically determined to realize a high shear strength without solder material atoms diffusing to adhesion layers. Molecular dynamics (MD) simulations and energy dispersive x-ray (EDX) spectrometry done after the shear tests clarified the eutectic reaction of the solder materials used in this research. Energy relaxation calculations in MD showed that the diffusion of solder material atoms into the adhesive layer was promoted at a higher temperature. Tensile creep MD simulations also suggested that the local potential energy in a solder material model determined the fracture points of the model. These numerical results were supported by the shear tests and EDX analyses for WLP accelerometers. Consequently, a bonding load of 9.8 kN and temperature of 300 °C were found to be rational conditions because the shear strength was sufficient to endure the polishing process after the WLP process and there was little diffusion of solder material atoms to the adhesion layer. Also, eutectic-bonding-based WLP was effective for controlling the attenuation of the accelerometers by determining the thickness of electroplated solder materials that played the role of a cavity between the accelerometers and lids. If the gap distance between the two was less than 6.2 µ m, the signal gains for x - and z -axis acceleration were less than 20 dB even at the resonance frequency due to air-damping.